PENGAJARAN KOSAKATA BAHASA INGGRIS MENGGUNAKAN MEDIA KOMPUTER DI SDN NEGERI 5 JEBUS KECAMATAN PARIT TIGA BANGKA BARAT - Sinta S; Maya Saftari; Yuni Iswanto (JURNAL PENGABDIAN MANDIRI, 2022)
Vocabulary means something that is crucial and very influential on all aspects of language skills, including reading skills. Students will be more practical to know a text if their vocabulary dominance level is high, and conversely they have difficulty understanding the text and quickly get bored of reading if they only know a little vocabulary. Without vocabulary a language will not function properly, structure and grammar cannot be used. Without structure and grammar one can still convey a little message, but without vocabulary no message can be conveyed. The language quality of students is determined by the quantity and quality of vocabulary. Given the importance of term vocabulary in language, vocabulary learning needs to be done in English learning